Recent Advances in Phytochemistry - Phytochemical Society of North America; Plant Phenolics Group of North America (New York : Academic Press, Inc., 1968)
Vol. 1 is the Proceedings of the 6th annual symposium of the Plant P henolics Group of North America, 1966; vols. 2-<5> are the Proceedings of the annual symposium of the Phytochemical Society of North America, 1967-<70>
Vol. 1 is the Proceedings of the 6th annual symposium of the Plant P henolics Group of North America, 1966; vols. 2-<5> are the Proceedings of the annual symposium of the Phytochemical Society of North America, 1967-<70>
Keywords: Botanical chemistry